KDM6B promotes PARthanatos via suppression of O6-methylguanine DNA methyltransferase repair and sustained checkpoint response. Issue 11 (1st June 2022) - Yang, Mingming; Wang, Chenliang; Zhou, Mi; Bao, Lei; Wang, Yanan; Kumar, Ashwani; Xing, Chao; Luo, Weibo; Wang, Yingfei
Abstract: Poly(ADP-ribose) polymerase-1 (PARP-1) is a DNA damage sensor and contributes to both DNA repair and cell death processes. However, how PARP-1 signaling is regulated to switch its function from DNA repair to cell death remains largely unknown. Here, we found that PARP-1 plays a central role in alkylating agent-induced PARthanatic cancer cell death. Lysine demethylase 6B (KDM6B) was identified as a key regulator of PARthanatos. Loss of KDM6B protein or its demethylase activity conferred cancer cell resistance to PARthanatic cell death in response to alkylating agents. Mechanistically, KDM6B knockout suppressed methylation at the promoter of O 6 -methylguanine-DNA methyltransferase (MGMT) to enhance MGMT expression and its direct DNA repair function, thereby inhibiting DNA damage-evoked PARP-1 hyperactivation and subsequent cell death. Moreover, KDM6B knockout triggered sustained Chk1 phosphorylation and activated a second XRCC1-dependent repair machinery to fix DNA damage evading from MGMT repair. Inhibition of MGMT or checkpoint response re-sensitized KDM6B deficient cells to PARthanatos induced by alkylating agents. These findings provide new molecular insights into epigenetic regulation of PARP-1 signaling mediating DNA repair or cell death and identify KDM6B as a biomarker for prediction of cancer cell vulnerability to alkylating agent treatment.